Refreshing medical students’ intravenous-cannulation skills: a blinded observer three-arm randomised comparison of mental imagery, part-task trainer simulation and written instructions - Robert Greif; Joana Berger-Estilita; Rafael Blülle; Daniel Stricker; Mathias Balmer; Christoph Berendonk (BMJ Open)
Introduction Intravenous cannulation is a core competence in medicine, but is considered challenging to learn. This study investigates the effectiveness of three educational strategies used to refresh the intravenous cannulation skills of first-year medical students: mental imagery, part-task trainer simulation and written instructions.Materials and methods In this single-centre randomised controlled trial, first-year medical students were assigned to one of three different refresher tutorials on intravenous cannulation. Six months after their compulsory 4 hour instructor-led intravenous-cannulation course, each student was randomised to a 6 min self-learning tutorial: a mental imagery audioguide session, hands-on intravenous cannulation on a part-task trainer or reading written instructions.Immediately after the refresher tutorials, trained evaluators who were blinded to the randomised group assessed the students’ performance. Each evaluator completed a 15-item standardised checklist in an Objective Structured Clinical Examination (OSCE) station for intravenous cannulation. We performed a descriptive analysis of the data and a one-way analysis of variance. Additionally, we investigated the influence of previous intravenous cannulation experience on the total OSCE score.Results and discussion On analysing the 309 students’ results, we did not find differences in the total rating of the performance (in percentage) between the three groups at the OSCE station (mental imagery group: 72.0%±17.9%; part-task trainer group: 74.4%±15.6%; written instructions group: 69.9%±16.6%, p=0.158). Multiple linear regression showed a small but statistically significant effect of students’ previous intravenous cannulation experience on OSCE performance. With the same outcome, written instructions and mental imagery had a better return on effort, compared with resource-intensive hands-on training with part-task trainers.Conclusion A single, short refresher seems to have a limited effect on intravenous-cannulation skills in first-year medical students. Less resource-intensive interventions, such as written instructions or mental imagery, are effective compared with hands-on part-task trainer simulation for refreshing this simple but important skill.Trial registration number AEARCTR-0008043.